ANALISIS RAMADHAN EFFECT PADA ABNORMAL RETURN SUBSEKTOR FOOD AND BEVERAGES DI BURSA EFEK INDONESIA (BEI) - Rizky Akbar (2021)
This study aims to analyze market anomalies, namely the Ramadhan Effect, on 13 food and beverages subsector listed consistently in the Indonesia Stock Exchange from 2016 to 2020. The independent variables in this study are daily returns and the dependent variable is abnormal return. The analysis was carried out using an event study consisting of three estimation models, namely the market model, constant mean model, and market adjusted model and the t significance test was carried out on cumulative abnormal return (CAR) with significance level 5% (0,05) using Eviews 10 software. Based on a step of analyzes that have been conducted, Ramadan has proven to be able to affect the psychology of investors and their decisions to invest. However, based on the t significance test carried out on the three estimation models (market model, constant mean model, and market adjusted model), the results of the Ramadhan Effect in the food and beverages sub-sector were not found or the Ramadhan effect was concluded that its existence was not strong enough. This is indicated by the inconsistent results of the three estimation models at the 5% significance level of cumulative abnormal return (CAR).